1989
DOI: 10.1111/j.1944-9720.1989.tb02746.x
|View full text |Cite
|
Sign up to set email alerts
|

Content‐Based Instruction for Foreign Language Classrooms

Abstract: Content‐based instruction (CBI) is a communicative approach to language teaching that is growing in popularity in both government and academic foreign language cides. The authors define CBI as a curriculum that 1) is based on subject matter, 2) utilizes authentic materials, 3) promotes the learning of new information, and 4) considers specific students' needs. Examples of CBI programs are provided. The Russian and Spanish CBI programs at the Foreign Service Institute are discussed in depth. Readers are request… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
0
2

Year Published

1992
1992
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 5 publications
0
46
0
2
Order By: Relevance
“…CBI teaching idea was explained and divided into 3 modes: sheltered model, adjunct model, theme-based model (Brinton, 2010). CBI was summarized 4 characteristics: (1) the subject content as the core; (2) the use of authentic language materials; (3) learning new information; (4) the curriculum must conform to different groups of students (Leaver & Stryker, 1989). The "6T" method of CBI was put forward, such as themes, texts, topics, threads, tasks and transitions (Stroller, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…CBI teaching idea was explained and divided into 3 modes: sheltered model, adjunct model, theme-based model (Brinton, 2010). CBI was summarized 4 characteristics: (1) the subject content as the core; (2) the use of authentic language materials; (3) learning new information; (4) the curriculum must conform to different groups of students (Leaver & Stryker, 1989). The "6T" method of CBI was put forward, such as themes, texts, topics, threads, tasks and transitions (Stroller, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It is mentioned by most of the scholars in this area that content-based instruction (CBI) supports to realize both content and language objectives and reach its goals. Many researchers have investigated about effectiveness of content-based instruction: e.g., Brinton & friends, 1989;Met, 1999;Leaver & Stryker, 1989;Dupuy, 2000), lack of collaboration between content and language teachers (Tan, 2011), the need for a more explicitly reflexive model of the relationship between content, language and learning (Barwell, 2006) and promoting content and language learning (Stoller, 2002). Stoller (2002) also showed that CBI has a great potential to promote content and language learning.…”
Section: Introductionmentioning
confidence: 99%
“…The three model was unable to fulfill the bilingual teaching of international law because of their advantages and disadvantages [7].…”
Section: The Problems In Bilingual Teaching Of International Businessmentioning
confidence: 99%